The Oxford-Diamond In Situ Cell for studying chemical reactions using time-resolved X-ray diffraction. - Moorhouse, S; Vranješ, N; Jupe, A; Drakopoulos, M; O'Hare, D (2012)
A versatile, infrared-heated, chemical reaction cell has been assembled and commissioned for the in situ study of a range of chemical syntheses using time-resolved energy-dispersive X-ray diffraction (EDXRD) on Beamline I12 at the Diamond Light Source. Specialized reactor configurations have been constructed to enable in situ EDXRD investigation of samples under non-ambient conditions. Chemical reactions can be studied using a range of sample vessels such as alumina crucibles, steel hydrothermal autoclaves, and glassy carbon tubes, at temperatures up to 1200 °C.